Systemic Inflammation Is Associated With Longitudinal Changes in Cognitive Performance Among Urban Adults - Beydoun, May A.; Dore, Gregory A.; Canas, Jose-Atilio; Liang, Hailun; Beydoun, Hind A.; Evans, Michele K.; Zonderman, Alan B. (Frontiers in Aging Neuroscience, 2018)
OBJECTIVES/BACKGROUND: Systemic inflammation can affect cognitive performance over time. The current study examined associations between systemic inflammation and cognitive performance among African Americans and Whites urban adults, stratifying by sex and age group and by race. PATIENTS/METHODS: Among 1,555-1,719 White and African-American urban adults [Agebase: 30-64y, 2004-2013, mean±SD follow-up time(y): 4.64±0.93y], conducted linear mixed-effects regression models were conducted to test associations of inflammatory markers [C-reactive protein, Erythrocyte Sedimentation Rate (ESR), albumin, iron and an inflammation composite score (ICS)] with longitudinal cognitive performance. RESULTS: Among key findings, CRP was linked to poorer baseline mental status among younger women (≤50y, γ01=-0.03±0.01, p=0.002) and poorer attention in older women (>50y, γ01=-0.024±0.007, p<0.004) and African-Americans (γ01=-0.029±0.008, p<0.001). ESR was related to faster decline on verbal memory among older men (>50y, γ11=-0.008±0.003, P=0.009); with poorer performance on attention tests overall (γ01=-0.010±0.003, P=0.003) and among African-Americans (γ01=-0.013±0.004, P=0.002); on verbal fluency among older women (>50y ,γ01=-0.037±0.013, P=0.004) and on executive function: overall (γ01=+0.62±0.21, P=0.004), older men (>50y, γ01=+1.69±0.53, P=0.001) and African-Americans (γ01=+0.84±0.28, P=0.002). Albumin was linked to slower attention decline among older men (>50y, γ11=+0.329±0.103, P=0.009), over-time improvement in executive function overall (γ11=-6.00±2.26, P=0.008), and better baseline psychomotor speed among African-Americans (γ01=+0.56±0.19, P=0.003). Finally, ICS predicted faster decline on visual memory/visuo-constructive abilities among older men (>50y, γ11=+0.17±0.06, p=0.003). CONCLUSION: In sum, strong associations between systemic inflammation and longitudinal cognitive performance were detected, largely among older individuals (>50y) and African-Americans. Randomized trials targeting inflammation are warranted.